2008
DOI: 10.1038/sj.bjc.6604466
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukaemia: long-term excess mortality and the proportion ‘cured’

Abstract: Survival from childhood leukaemia has increased, but the proportion of children cured is unknown. The proportion 'cured' is defined as the proportion of survivors for whom, as a group, there is no longer excess mortality compared to the general population. Average time to cure is defined as the time since diagnosis at which the excess mortality rate has declined to or below a predetermined small value. Data on children diagnosed with leukaemia during 1971 -2000 in Great Britain were used to estimate trends in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
(21 reference statements)
2
15
0
1
Order By: Relevance
“…Due to improved therapy, 80 % of the children diagnosed with cancer will become long-term survivors [33]. Long-term survivors of childhood cancers are at increased risk of late mortality compared with the general population mainly due to treatment-related secondary neoplasms, and cardiac, and pulmonary deaths [31,[34][35][36][37]. A Nordic study by Moller et al [6] reported a reduction in the overall late mortality among long-term childhood cancer survivors over time.…”
Section: Comparison With the Literaturementioning
confidence: 97%
“…Due to improved therapy, 80 % of the children diagnosed with cancer will become long-term survivors [33]. Long-term survivors of childhood cancers are at increased risk of late mortality compared with the general population mainly due to treatment-related secondary neoplasms, and cardiac, and pulmonary deaths [31,[34][35][36][37]. A Nordic study by Moller et al [6] reported a reduction in the overall late mortality among long-term childhood cancer survivors over time.…”
Section: Comparison With the Literaturementioning
confidence: 97%
“…The dramatic improvement in survival from childhood leukaemia in the UK since the 1970s1 can be attributed to the protocol improvements fostered by clinical trials and the extension of the best treatments to a higher proportion of patients through referral to specialist treatment centres 18. Currently over 90% of children with cancer are treated in these centres19 where a wide portfolio of clinical trials is available, and non-participants are usually treated on the current best standard treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Survival and cure rates for childhood lymphoid leukaemia and acute myeloid leukaemia (AML) have increased dramatically in the UK since the 1970s 1 2. This success has been attributed to a series of national clinical trials and the development of specialist treatment centres.…”
Section: Introductionmentioning
confidence: 99%
“…15 Similarly, in a British childhood cancer survivor study with a mean follow up of 25 years, the stanPediatric and adolescent ALL in Europe haematologica | 2013; 98 (5) 747 Kingdom 967 963 1136 1198 1181 1221 1237 Under 1 year 29 39 40 41 41 32 38 1-4 years 498 497 573 597 576 564 564 5-9 years 246 267 272 302 303 346 320 10-14 years 194 160 159 153 187 197 218 15-19 years --66 69 47 56 57 20-24 years --26 36 27 26 40 dardized incidence ratio of subsequent primary neoplasms was 4.3. 16 Shah et al 6 found that both survival and the proportion of children cured of lymphatic leukemia had increased, but the excess mortality of patients had spread over a longer period of time: from 11 years after diagnosis for children diagnosed in 1971-75, to 16 years for those diagnosed in 1986-1990. It was suggested that secondary malignancy and treatment-related toxicity were the reasons for the persisting excess mortality.…”
Section: Proportion Cured According To European Region and Agementioning
confidence: 99%
“…However, for several of these cancers, including ALL, an excess risk of death persists for five years and over after diagnosis. 4,5 A new indicator of outcomes in children (the estimated proportion of cured cases) was first used by Shah et al 6 in UK children with acute lymphoblastic leukemia. The proportion of cured cases is estimated by cure models.…”
Section: Introductionmentioning
confidence: 99%